Türkiye ve uluslararası Bauhaus sanat ve tasarım fakültelerinde grafik eğitimi program içerikleri ve işleyişler - Kara, İlke Meltem (My University, 2009)
II SUMMARY Art of graphic, which is an important communication field, is a field of art where aesthetics and technology connecting broad masses are inside to inside. “Graphical design is a visual communication art. Its first function is to convey a message or to introduce a product or service.”1 Graphical art products prepared by graphical artist are conveyed to large masses by means of printing and reproduction technique. Today development of graphic design and designer in the world does not solely rely on reproduction techniques. Graphical art and graphical designer also focus on basic problems of the vocation, visual communication designs and visual communication solution. Graphical design adopts various printing and reproduction techniques as method. Nevertheless, the real thing that graphical designer has to develop and focus on is to acquire functional, socio psychological, and social information that is required for effective use of visual communication. Along with designer’s gaining intellectual and cognitive skills, graphical designs created, regardless of their technique and type, serves as a mirror that reflects the innovations, lifestyles, and admirations of its age and that presents new lifestyles to the community. Designer will fulfill its function of facilitating daily life by selecting right plastic components, and by playing an important role in mass communication. Graphic designer is not interested in aesthetic values solely; designer informs masses, draws attention, educates and forces others to think by adding new values to world with his/ her designs. “Read said: “Design 1 Emre Becer “ iletişim ve Grafik Tasarım”,Ankara,, Dost Kitabevi,2005,s:37 III is much more than combining, arranging and editing. It is giving a value and meaning …”2. Graphical design education has to develop a method of critic that is compliant with communication tools used. In addition to inner talent, student must be educated by knowledge, sense, and comprehension of humanly physical, social and cultural factors. Although trial included in Bauhaus education system will make development of new manifests in performance improvement, application method, and design education possible, it will also enable new definitions and uses of communication factors such as images, text, voice, movement, and time. Common relationship of Bauhaus schools that were established in 1919 in Weimar, Germany for purpose of providing education in arts and design can be summarized as making a dead industrial product breath.”3 Bauhaus education system aims to develop solutions to communities issues by building the responsibility of thinking and designing on current issues of the society. “Most important component that steered the shape had to be function. Formulating this approach as “form follows function” was the purpose of Bauhaus...”4 Today, institutions that provide education on basis of Bauhaus philosophy continue this philosophy by use of advancing technologies of the age in education system. After Bauhaus school was closed in 1933 upon Nazi’s pressure, Devlet Tatbiki Güzel Sanatlar Yüksek Okulu (State College of Practical Fine Arts) (DTGSYO) in 1957 in Turkey by Prof. Dr. Engineer-Architect Adolf 2 Devabil Kara, “ Sanatcı Kişiliğinde Psikoloji” (Psychology of Artistic Identify), Marmara University Institute of Social Sciences, Painting Department, Artistic Doctorate Dissertation, Istanbul, 1993 3 Emre Becer.Agg, s.103 4 Agg.s:103 IV Schneck. Consisting of decorative painting, graphical arts, furniture and interior design, ceramic arts, and textile arts, DTGSYO has introduced Bauhaus education system to our country. Having adapted master-pupil approach to modern education, Bauhaus education system has provided education opportunity to many valuable designers, artists, and educators in our country. Advertisement agencies, interior design offices, and ceramic design companies were put in to practice upon the commencement of this education process in our country. Education systems and curriculums of institutions that were established on basis of Bauhaus school, which had important direct effects on social life, are included in the scope of this study. The purpose of this study is to research the similarities and differences of leading institutions that implement Bauhaus education system in our country with those institutions that provide education on basis of the aforementioned education system, to demonstrate the differences in manner of Bauhaus institutions from the past until today, and to compare the education systems of these institutions.
Keywords: Grafik; Grafik Eğitimi; Tasarım